2015
DOI: 10.1088/0963-0252/24/3/032001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of magnetic field and density on the streaming instability in magnetized pair plasmas

Abstract: The influence of magnetic field and density on the streaming instability in the electronpositron plasma with the moving ion fluid in a magnetic field is investigated. The analytic expressions of the growth rate and oscillating frequency of the streaming instability are obtained as functions of the cyclotron frequency, electron density, positron density, ion density, streaming velocity, and wave number. The variation of the growth rate and oscillating frequency of streaming instability due to the change of magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Recently, the investigation of dense semi-classical or quantum plasmas has received a considerable attention since the dense degenerate plasma is found in modern science and technology such as nano-plasma, quantum-dot, and quantum-well, etc [22][23][24][25][26][27]. Moreover, the streaming instability has been of a great interest in plasmas since it is shown that the instability condition provides a useful information on the characteristics and properties of the plasma configurations with streaming components [28][29][30]. Hence, the investigation on the damping rate and the propagation of the surface waves propagating on the interface of the streaming dense semi-classical or quantum turbulent plasmas will be treated elsewhere since the companion of the quantum-mechanical and turbulence effects will produce unique phenomena on the damping rate of the surface wave in dense semi-classical or quantum turbulent plasmas.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the investigation of dense semi-classical or quantum plasmas has received a considerable attention since the dense degenerate plasma is found in modern science and technology such as nano-plasma, quantum-dot, and quantum-well, etc [22][23][24][25][26][27]. Moreover, the streaming instability has been of a great interest in plasmas since it is shown that the instability condition provides a useful information on the characteristics and properties of the plasma configurations with streaming components [28][29][30]. Hence, the investigation on the damping rate and the propagation of the surface waves propagating on the interface of the streaming dense semi-classical or quantum turbulent plasmas will be treated elsewhere since the companion of the quantum-mechanical and turbulence effects will produce unique phenomena on the damping rate of the surface wave in dense semi-classical or quantum turbulent plasmas.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, for a semi-bounded dusty Lorentzian plasma containing streaming ions, the resonant instability growth rate was previously obtained [14]. If we take the thermalized electrons by letting the spectral index in the Lorentzian velocity distribution be infinity in [14], the result would be the same as equation (12).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…It is well known that a beam of charged particles traveling through a plasma can be a source of instability due to the beam-wave interaction. This so-called streaming instability has attracted considerable interest in various plasmas because the instability condition has provided useful information on the physical characteristics and properties of plasma systems with streaming plasma components [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] Later, various wave dispersions and instabilities were discussed in the cold, magnetized, and counter‐streaming electron–positron plasma, and the results were applied to an oscillating model for a pulsar magnetosphere. [ 10 ] Furthermore, how the magnetic field and positron concentration affect the growth rate of ion‐streaming instability in e‐p‐i magnetized plasma [ 11 ] was also investigated. The investigations of ion cyclotron streaming instability in e‐p‐i plasma was presented, and the growth rates of the instability for unidirectional streaming and counter‐streaming of electrons and positrons were compared.…”
Section: Introductionmentioning
confidence: 99%